Investment Readability Through The Digital Platform - Itzhak Vici; Nuryasman MN (Jurnal Ekonomi, 2022)
In this modern era, technology had so much improvement so as in investment, there is so many online-investment now a days from illegal investment to trusted investment approved by government. There is a tremendous amount of investment fraud that make society doubtful to do online investment, especially for student which have a limited source of money. But it will be different if the individual had a basic knowledge in financial and investment, even more the information of investment and financial support them whatsmore the confidence in each individual to make decision for their own money. That kind of factors will increase student interest on investment. The purpose of this research to know the influence of financial inclusion, financial literacy, financial self-efficacy and investment knowledge towards investment interest of economic students in Tarumanagara University through digital platform. Researchers used primary data by distributing questionnaires to all economic students in Tarumanagara University with a sample of 100 respondents using purposive sampling The data analysis method in this study is a quantitative method using Structural Equation Modeling (SEM), which is processed with the help of SmartPLS software version 3.3.3. The results of this study indicate that financial inclusion, financial literacy, financial self-efficacy and investment knowledge have significant and positive effect on interest investment of economic students in Tarumanagara University thorugh digital platform.